Non-convulsive Status Epilepticus in Children, Electro-Clinical Profile and Response to a Specific Treatment Protocol - Banu, Selina Husna; Mahbub, Mostafa; Azam, AZM Moshiul; Rani, Shipra; Khan, Naila Z (Bangladesh Journal of Child Health, 2010)
Objective: Non-convulsive status epilepticus (NCSE) is an under-diagnosed neurological condition. We report the electroclinical profile and treatment outcome of children diagnosed with NCSE. Methods: Total 45 children were identified with NCSE at the EEG laboratory from September 2004 to January 2009. Their presenting complaints, past clinical and birth related information were meticulously recorded. On diagnosis the referring physicians were requested to repeat the test after starting treatment. Later they were treated with a specific protocol on admission at the Neurology Unit of Dhaka Shishu Hospital. Two lines of treatment with daily routine EEGs were introduced. Electroclinical outcome were recorded on discharge. The children are still on regular follow up to record the long-time result of the protracted treatment. Results: Motor regression and postural problem were the primary complaints in the majority (37/45, 82%) followed by involuntary movement, muscle twitching, jerks or frequent fall (31/45, 69%), speech regression (29, 64%) and change of usual behavior (25/45, 56%). Prior major seizures (generalized tonic clonic, tonic or clonic) was reported in 32/45, 71%, within 1 week to 1 year. Initial diagnosis was multiple including hysteric conversion reaction, post-ictal regression or neuro-degenerative disorder. None was suspected with NCSE. Diagnosis was confirmed by the EEG finding of continuous generalized (82%) or localized (18%) slow spike-wave complexes. On protracted treatment, 82% achieved the target. Conclusion: NCSE is common in children, may occur de-novo. The variable phenotype may lead to erroneous diagnosis. A protracted treatment protocol is suggested. Further reporting on this issue will help to assist the clinicians for early-diagnosis and treatment. Key words: non-convulsive status epilepticus; electro-clinical diagnosis; motor functional regression; speech regression; behavioural changes. DOI: 10.3329/bjch.v33i3.5689 Bangladesh Journal of Child Health 2009; Vol.33(3): 90-99